The gender challenge of Hebrew - Muchnik, Malka. (The Brill Reference Library of Judaism, 2015)
The Gender Challenge of Hebrew is the first book to delve in depth into the problem of gender representation over the 3,000-year history of the Hebrew language. By analyzing and illustrating the grammatical characteristics of gender in Biblical, Mishnaic, Medieval and Modern Hebrew, Malka Muchnik reveals the social and cultural issues that they reflect. Gender discrimination in all periods of Hebrew is shown in sacred, liturgical and literary texts, as well as in the popular language spoken today. All of them testify to the problematic status of women, who were traditionally excluded from religious studies and public activities, and in recent decades have been struggling to change this practice. Malka Muchnik shows that linguistic change remains a challenging goal.